The spectrum of α- and β-thalassemia mutations of the Li people in Hainan Province of China - Yao, Hongxia; Chen, Xinping; Lin, Lie; Wu, Congming; Fu, Xiangjun; Wang, Hua; Yao, Zhiming; Chen, Wenting; Huang, Li; Tang, Ruimei; Rao, Ruo; Wang, Suwen; et al. (Blood cells, molecules, & diseases, 2014)
This study examines the frequency and spectrum of α- and β-thalassemia (thal) mutations of the Li people in Hainan Province of China. We have analyzed by genotyping a sample of 8600 subjects of the Li people and found that 53.45% subjects have only α-thal mutations with high frequencies of −α4.2 and −α3.7, but fewer −−SEA mutation; 3.83% have β-thal mutations all identified to be 41/42 (−TCTT); whereas 7.99% carry both α-thal and β-thal mutations. We also examined 9800 subjects of the Han people, and the result showed 12.16% subjects have only α-thal mutations with −−SEA and −α3.7 the most frequent mutation types, 6.11% have only β-thal mutations of 7 types, whereas 4.85% carry both α-thal and β-thal mutations. Our study demonstrated that the Li people in Hainan province have a high incidence of −α4.2 and −α3.7 thalassemia, low frequencies of α-thal −SEA, and a novel β mutation, 41/42 (−TCTT). We provide the complete spectrum of α-thal and β-thal mutations and a strategy for accurate molecular diagnostic testing in the Li people in Hainan Province of Southern China.